Capturing agro-morphological variability for tolerance to terminal heat and combined heat–drought stress in landraces and elite cultivar collection of wheat - Kumar, Shubham; Kumar, Hitesh; Gupta, Vikas; Kumar, Adesh; Singh, Chandra Mohan; Kumar, Mukul; Singh, Ajay Kumar; Panwar, Gurusharan Singh; Kumar, Sujit; Singh, Akhilesh Kumar; Kumar, Rahul (Frontiers in Plant Science, 2023)
Climate change has resulted in extreme temperature and drought around the globe which poses serious threat to food security. Both heat and drought stress affects the production and productivity of wheat crop. The present study was undertaken to evaluate thirty-four landraces and elite cultivars of Triticum spp. for phenological and yield related traits under optimum, heat and combined heat-drought stress environments during 2020-21 and 2021-22. The pooled analysis of variance showed significant genotype x environment interaction suggesting an influence of stress on trait expression. The trait performance of genotypes exhibited significant reduction under combined heat-drought stress as compared to optimum and heat stress environments. The maximum seed yield penalty was observed under combined heat-drought stress environment as compared to heat stress alone. Regression analysis indicated significant contribution of number of grains per spike towards stress tolerance. Based on Stress Tolerance Index (STI), genotypes Local-17, PDW 274, HI-8802 and HI-8713 were identified to be tolerant to both heat and combined heat and drought stress at Banda whereas, genotypes DBW 187, HI-8777, Raj 4120 and PDW 274 were tolerant at Jhansi location. The genotype PDW 274 showed stress tolerance under all treatments at both the locations. The genotypes PDW 233 and PDW 291 showed highest stress susceptibility index (SSI) across the environments. The number of grains per spike and test kernel weight were positively associated with seed yield across the environments and locations. The selected genotypes Local-17, HI 8802 and PDW 274 were identified to be the potential sources of heat and combined heat-drought tolerance which may be utilized in hybridization to develop tolerant wheat genotypes and also for mapping of underlying genes/QTLs.